Persepsi Karyawan Untuk Meningkatkan Servant Leadership - Nyoman Sri Manik Parasari; Ni Putu Nina Eka Lestari (Jurnal Manajemen dan Bisnis, 2015)
This research aims to know how employee’s perception to improve servant leadership(Study at RSUD Wangaya Denpasar) also how application servant leadership based onPatterson Theory. This research used qualitative method by doing depth interview towardsseven employees as informant.Based on interview can be stated that perception owned by employees RSUDWangaya Kota Denpasar is really required in performing work, because by existence abouthow application servant leadership will be improved as according to procedures aboutquality and benefit servant leadership to all society. Actually, Servant Leadership isleadership culture exist on Christianity teaching. Servant leadership, mainly in Balifrequently known as term”Meyadnya” meansholy sacrifice perfomed sincerely in Hinduteaching. Servant Leadership already performed by RSUD Wangaya Kota Denpasar and somany changes done by this hospital. Servant leadership is fully proven made RSUD WangayaKota Denpasar as reference hospital that always ready to give service. Approach usedPatterson Theory also really related to how servant leadership can be done at RSUDWangaya Kota Denpasar, which our love in giving best service really needed by many thattake healing at RSUD Wangaya Kota Denpasar. Each employees should be humble and workwithout ego owned. Application Servant Leadership should be in way of sincere, withoutexpecting and return from society. Moreover, having strong self esteem with leader,employeeand societythat come to heal at RSUD Wangaya Kota Denpasar.Keywords : Employee Perception, Servant Leadership.